How to Talk to Your Son about Fascism - Johnson, Craig A. (Routledge, 2025)
How to Talk to Your Son about Fascism is a practical guide for parents, carers, and others with young men in their lives on how to talk with those young men about fascism and the right-wing, which specifically and particularly preys on them for recruitment. Its central goal is to present research, history, and analysis about how and why the right-wing recruits young men to parents, educators, and anyone with a young person in their lives. The book covers the history of right-wing recruitment of young men, explaining why the right-wing focuses on recruiting men both on a theoretical basis and through the logic of movement-building, and then moves to practical analysis and suggestions for how to counter recruitment today. Recommendations come from excerpts and existing scholarship. Readers will come out of the book with a better understanding of what fascism is and how it works, how it preys on young men, how it recruits and appeals to them, and how to stop this from happening. This book will be of interest to antifascist researchers and activists, as well as parents, carers, and the general reader concerned about the rise of the extreme right.
Keywords: Fascism.; elektronické knihy; electronic books